Agroforestry creates carbon sinks whilst enhancing the environment in agricultural landscapes in Europe - Sonja, Kay; Rega, Carlo; Moreno, Gerardo; den Herder, Michael; Palma, João H. N.; Borek, Robert; Crous-Duran, Josep; Freese, Dirk; Giannitsopoulos, Michail; Graves, Anil; Jäger, Mareike; Lamersdorf, Norbert; et al. (Elsevier, 2019)
Agroforestry, relative to conventional agriculture, contributes significantly to carbon sequestration, increases a range of regulating ecosystem services, and enhances biodiversity. Using a transdisciplinary approach, we combined scientific and technical knowledge to evaluate nine environmental pressures in terms of ecosystem services in European farmland and assessed the carbon storage potential of suitable agroforestry systems, proposed by regional experts. First, regions with potential environmental pressures were identified with respect to soil health (soil erosion by water and wind, low soil organic carbon), water quality (water pollution by nitrates, salinization by irrigation), areas affected by climate change (rising temperature), and by underprovision in biodiversity (pollination and pest control pressures, loss of soil biodiversity). The maps were overlaid to identify areas where several pressures accumulate. In total, 94.4% of farmlands suffer from at least one environmental pressure, pastures being less affected than arable lands. Regional hotspots were located in north-western France, Denmark, Central Spain, north and south-western Italy, Greece, and eastern Romania. The 10% of the area with the highest number of accumulated pressures were defined as Priority Areas, where the implementation of agroforestry could be particularly effective. In a second step, European agroforestry experts were asked to propose agroforestry practices suitable for the Priority Areas they were familiar with, and identified 64 different systems covering a wide range of practices. These ranged from hedgerows on field boundaries to fast growing coppices or scattered single tree systems. Third, for each proposed system, the carbon storage potential was assessed based on data from the literature and the results were scaled-up to the Priority Areas. As expected, given the wide range of agroforestry practices identified, the carbon sequestration potentials ranged between 0.09 and 7.29 t C ha−1 a−1. Implementing agroforestry on the Priority Areas could lead to a sequestration of 2.1 to 63.9 million t C a−1 (7.78 and 234.85
Keywords: Carbon storage; Climate change mitigation; Ecosystem services; Farmland; Resource protection; Spatial deficit analysis